Early Estimations of Dimensions for Prestressed Concrete Bridges - Optimization by Set-Based Parametric Design of Cross-Section and Prestressing Force in a Preliminary Stage - Aspegren, Daniel; Möörk, Erik (My University, 2021)
When designing concrete bridges, estimations of the dimensions and reinforcement content are made to estimate the cost of the bridge in an early phase. When the final bridge is designed, the estimated dimensions based on experience and simplification is often used and checked against the national regulations. If the dimensions comply with the regulations, the estimated design is used as the final design and there is not often time to reduce and optimize the dimensions to make the bridge more material efficient. This master thesis presents an optimization method for the early estimations of the design for continuous prestressed concrete bridges. This method is based on set-based parametric design and the optimization is performed with a python script where this method is implemented. The optimization is focusing on the relationship between beam height, number of prestressed tendons and the parabolic tendon layout with the aim to minimize the global warming potential (GWP) and cost for the superstructure. The script with the optimization method has been created to enable an effective approach to reach an optimized solution in the preliminary design phase, which will result in a more material efficient final bridge design. To reach the lowest GWP and cost, a slender cross-section with a large number of prestressed tendons is desirable. Depending on the case-specific conditions, the tendon layout is preferable designed in different ways. For shorter bridges, a tendon layout that is minimizing the secondary moment is preferable to obtain a slender cross-section, while for longer bridges the self-weight is increased and therefore a tendon layout that results in a larger secondary moment is the most favourable. The method was used to create designs which was compared with two existing bridges designed by Inhouse Tech Göteborg AB. The designs showed an improvement, for both cost and GWP compared to the existing bridges. Above all, there are opportunities for a more optimized and material-efficient design if the tendon layout is adapted to the case specific conditions.
Keywords: Prestressed concrete bridge, Preliminary design, Set-based parametric design, BRIGADE/Plus, Tendon layout, Optimization